Cerebral blood flow after carotid occlusion and extracranial-intracranial bypass. - Thomas, M (1984)
Eleven patients with occlusion of one internal carotid artery showed marked reduction of regional cerebral blood flow (rCBF) through the hemisphere on the affected side with high rCBF on the opposite side. Six of the patients had no surgery, during follow-up of 2 to 5 years. rCBF increased on both sides leaving a persisting asymmetry of rCBF. Five patients had extracranial-intracranial bypass; rCBF increased on the affected side but not on the opposite side. Asymmetry of rCBF between the hemispheres remained but was much less than in the non-operated group.